THE LINGUODIDACTIC SIGNIFICANCE OF MODERN INTERACTIVE METHODS IN TEACHING ENGLISH - Qodirova , Dilnura; Saitov , Sirojiddin (Scientific practical conference, 2026)
This article explores the linguodidactic significance of modern interactive methods in teaching English as a foreign language. In the context of globalization and the rapid development of digital technologies, the demand for effective and student-centered teaching approaches has significantly increased. The study analyzes the role of interactive teaching methods in enhancing learners’ communicative competence, critical thinking, and motivation. Special attention is given to methods such as group work, role-playing, problem-based learning, and digital tools integration. The article also examines the theoretical foundations of linguodidactics and highlights how interactive methods contribute to language acquisition. Furthermore, the research identifies key challenges in implementing these methods and proposes practical recommendations for educators. The findings demonstrate that modern interactive methods play a crucial role in improving the quality of English language teaching and fostering active learner engagement.